Law and its limitations in the GATT multilateral trade system - Long, Oliver (Mortinus Nijhoff Publishers DordrechtNL, 1985)
Examines basic rules and procedures that make up the GATT legal framework; the extent to which this framework has evolved and methodology used to introduce necessary reforms. Brief consideration is given to participation of nen-GATT countries in GATT negotiations. Also examines areas viz. treaty enforcement despite settlement procedures and differential and more favourable treatment for developing countries.